Penguatan Pendidikan Karakter Berbasis Islam: Tinjauan Dari Perspektif Pendidikan Dan Psikologi Islam - Desi Lestari; Reza Obi Mayu; Fanny Septi Wulandari; Ageel Saputra; Akhirul Ramadhani; Ahmad Yusuf; Deni Andika; Roihan Masyhuri Lubis; Septian May Paroz; Afzal Fikri Hartono; Raja Pande Munthe; Hendri Ardiansah; M Nur Kholis; Chanda Aprilindra (AL-MIKRAJ Jurnal Studi Islam dan Humaniora, 2025)
This study aims to examine the strengthening of Islamic-based character education through a literature study approach, by tracing the relationship between Islamic values ​​and the Islamic psychology approach in shaping students' personalities. The method used is descriptive qualitative with content analysis techniques on scientific literature published in 2018–2025. The results of the study found ten main themes that underlie the formation of Islamic character, including the values ​​of monotheism, the morals of the Prophet Muhammad, purification of the soul (tazkiyatun nafs), habituation of worship, spiritual balance, and teacher role models. Character in Islam is seen as a manifestation of spiritual, moral, and emotional integrity, not just normative behavior. This study concludes that the success of character education is largely determined by the synergy between the roles of teachers, families, and curriculum that are integrated and relevant to the challenges of the digital era. Therefore, an adaptive education strategy is needed but still rooted in Islamic values, as well as training for teachers and parents as moral role models. This study confirms that the Islamic-based character education approach can be a conceptual solution in addressing the moral crisis among the younger generation.